PERBANDINGAN PENGGUNAAN AGREGAT KASAR DAN HALUS YANG BERASAL DARI PEGUNUNGAN NARU DAN SUNGAI LEKO ENA PADA MUTU BETON fcâ=19,3 - Deri, Eusabius Ignasius; Rasidi, Nawir; Ningrum, Diana (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Aggregate Naru mountain and river Ena Leko became an important commodity in Ngada and surrounding counties, namely as a building material. aggregate must meet the technical requirements, but as a natural ingredient of quality aggregates and Leko Ena Naru obviously heavily influenced by the state of the environment and the place they were taken. The study was conducted in Laboratory with concrete cube 15 x 15 cm to determine the compressive strength of concrete and the cylinder with a size of 15 x 30 cm for tensile strength of concrete. Where to concrete compressive strength test specimens made of 8 pieces for mountain aggregate Naru and 10 bauah specimen cube to aggregate Leko Ena river. While the tensile strength of concrete specimen 5 pieces for each type of aggregate with a mixture of 1 cement ratio: 1.65 Gravel: and 2.47. Preliminary test of the aggregate of the mountain naru showed that the compound was 00:36 % water, coarse aggregate specific gravity and density of 2:47 to 2:53 fine aggregate, coarse aggregate absorption amounted to 2:32 % and fine aggregate is 21.70 %. Los Angelos Abrasion Test with the engine at a speed of 30-33 rpm was 55.45 %. Compressive strength of concrete at the age of 7 days converted to 28 days for 197.88 Kg/cm2, Naru Quality material is used as a concrete class 1 ( Bo and B1 ), but for concrete grade 2 can still be used even seen any of the terms of abrasion it is not justified, because it exceeds the SNI requirements by 40 %. As for the aggregate stream Ena Leko showed that the water content was 0.359 %, 0.240 specific gravity of coarse aggregate and fine aggregate specific gravity of 2.437, for the absorption of 2:32 % coarse aggregate and fine aggregate is 21.70 %. Compressive strength of concrete at the age of 7 days converted to 28 days for 100.74 Kg/cm2. Keywords: Quality Aggregate, Concrete Compressive Strength, tensile strength of concrete, Naru, Leko Ena ABSTRAK Agregat gunung Naru dan sungai Leko Ena menjadi komoditas penting di kabupaten Ngada dan sekitarnya, yaitu sebagai bahan bangunan. agregat harus memenuhi berbagai syarat teknis, Namun sebagai bahan alam kualitas agregat Naru dan Leko Ena jelas banyak dipengaruhi oleh keadaan tempat dan lingkungan pengambilannya. Penelitian dilakukan di laboratorium dengan kubus beton 15 x 15 cm untuk mengetahui kuat tekan beton dan silinder dengan ukuran 15 x 30 cm untuk kuat tarik beton. Dimana untuk kuat tekan beton dibuat 8 buah benda uji untuk agregat gunung Naru dan 10 bauah benda uji kubus untuk agregat sungai Leko Ena. Sedangkan kuat tarik beton 5 buah benda uji untuk masing-masing jenis agregat dengan Perbandingan campuran 1 semen : 1,65 Kerikil : 2,47 Pasir. Uji pendahuluan terhadap aggregat dari gunung naru menunjukan bahwa kandungan air adalah 0.36%, berat jenis agregat kasar 2.47 dan berat jenis untuk agregat halus 2.53, penyerapan untuk agregat kasar sebesar 2.32 % dan agregat halus adalah 21.70%,. Abrasi dengan mesin Los Angelos Test pada kecepatan 30-33 rpm adalah 55.45%. Kuat tekan beton pada umur 7 hari dikonversi ke 28 hari sebesar 197,88 Kg/cm2, Kualitas material Naru dipergunakan sebagai beton kelas 1 (Bo dan B1), tapi untuk beton kelas 2 pun masih dapat digunakan walaupun dilihat dari syarat abrasi hal itu tidak dibenarkan, karena telah melampaui syarat SNI sebesar 40%. Sedangkan untuk agregat sungai Leko Ena menunjukan bahwa kandungan air adalah 0,359%, berat jenis agregat kasar 0,240 dan berat jenis untuk agregat halus 2,437, penyerapan untuk agregat kasar sebesar 2.32 % dan agregat halus adalah 21.70%,. Kuat tekan beton pada umur 7 hari dikonversi ke 28 hari sebesar 100,74 Kg/cm2, Kata Kunci : Kualitass Agregat, Kuat Tekan Beton,kuat tarik beton, Naru, Leko Ena